Bates' pocket guide to physical examination and history taking - Bickley, Lynn S.; Bickley, Lynn S. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"This concise pocket-sized guide presents the classic Bates approach to physical examination and history taking in a quick-reference outline format. It contains all the critical information needed to obtain a clinically meaningful health history and tconduct a thorough physcial assessment. Fully revised and updated, the Seventh Edition will help health professionals elicit relevant facts from the patient's history, review examination procedures, highlight common findings, learn special assessment techniques, and sharpen interpretive skills.The book features a_vibrant full-color art program and an easy-to-follow two-column format with step-by-step examination techniques on the left and abnormalities with differential diagnoses on the right" Provided by publisher.
Abridgement of: Bates' guide to physical examination and history-taking. 11th ed. / Lynn S. Bickley, Peter G. Szilagyi. c2013.
Includes bibliographical references and index.
Keywords: Medical History Taking -- methods -- Handbooks